Species Composition of Rays Caught by Fishermen Landed at Branta Coatal Fishing Port, Pamekasan - East Jawa - Riny Ayu Trian Putri; Husain Latuconsina; Hasan Zayadi (BIOSAINSTEK, 2026)
This study aims to analyze the species composition, catch targets, and conservation status of rays landed at the Fishing Port. This study was conducted for one month, namely March to April 2023, at the Branta Coastal Fishing Port in Pamekasan. The study was conducted through direct field observations with local communities regarding the location of stingray and shark fishing, as well as the fishing gear used. The samples obtained were immediately documented and recorded immediately after the fishing vessel arrived at the dock to obtain data. Descriptive analysis includes species composition, catch targets, prices and status. The results of the study obtained 96 specimens, from 3 species (Brevitrygon javaensis, Neotrygon kuhlii, Gymnura poecilura), 2 families (Dasyatidae, and Gymnuridae) and 1 order (Myliobatiformes). The highest number and composition of ray species are Javan Whipray (Brevitrygon javaensis) 79 species (82%), Bluespotted Stingray (Neotrygon kuhlii) 15 species (16%), and the lowest is Butterfly Stingray (Gymnura poecilura) 2 species (2%). All species are bycatch, and are included in three conservation status categories, namely Endangered (Brevitrygon javaensis), Vulnerable (Gymnura poecilura) and Data Deficient (Neotrygon kuhlii). Socialization efforts for various threatened and protected ray species are an important priority to support conservation strategies through measured fishing and trade regulations, supported by monitoring and evaluation and law enforcement.